2013
DOI: 10.1111/scs.12062
|View full text |Cite
|
Sign up to set email alerts
|

Zest for life among 65‐ and 75‐year‐olds in Northern Finland and Sweden – a cross‐sectional study

Abstract: In general, 65- and 75-year-olds in Finland and Sweden have a zest for life. Even though the study sample shows that only a small number of respondents have no zest for life, zest for life is a concept worth investigating in that there exists a strong association between no zest for life and depression. Physical and psychological health and well-being are important determinates of zest for life and, seemingly, a determinate for successful ageing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Contextual factors such as society and living environment influence older persons' experiences of their health and well‐being . Previous analyses of the GERDA project's data have shown that some differences do exist between the three included language groups regarding life orientation, zest for life, social networks and sense of security . Nyqvist et al found that Swedish speakers in Finland possess more structural and cognitive social capital than Finnish speakers and that social capital might to some extent explain the health differences seen between these two language groups.…”
Section: Discussionmentioning
confidence: 99%
“…Contextual factors such as society and living environment influence older persons' experiences of their health and well‐being . Previous analyses of the GERDA project's data have shown that some differences do exist between the three included language groups regarding life orientation, zest for life, social networks and sense of security . Nyqvist et al found that Swedish speakers in Finland possess more structural and cognitive social capital than Finnish speakers and that social capital might to some extent explain the health differences seen between these two language groups.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its potential sensitivity, the question referred to people in general rather than the willingness of the participant him- or herself to live up to 100 years. The dichotomous response (yes/no) was used as an indirect measure of zest for life and life satisfaction (Glasberg, Pellfolk, & Fagerström, 2014), one of the most frequently used components of successful aging (Depp & Jeste, 2006). Self-rated health and the opinion about living up to 100 years were asked only when the respondent him- or herself answered the questions.…”
Section: Methodsmentioning
confidence: 99%
“…Significant increases in self-efficacy and morale are also anticipated [44], as are possible decreases in loneliness, and possible cognitive inflammatory states and physiological dysregulation [45], and depression [46]. Self-compassion May benefit mental health/life quality Kima nd Ko [58] Self-esteem Can protect against fears concerning loneliness Rossie et al [69] Spirituality + religion May slow cognitive decline in dementia Agli et al [60] Visualizing best self May help to increase/sustain positive emotion Sheldon et al [61] Zest for life May help avert depression Glasberg et al [62] Table 1. Sample of empowerment-based positive psychology strategies directed at emotional regulation, and the generation of positive self-perceptions, and beliefs and affect that can learned as well be applied alone or in combination ©2021 Ray Marks.…”
Section: What the Research Showsmentioning
confidence: 99%